Online or physical class for histology course: Which one is better? - Yu-Hsueh Wu; Chun-Pin Chiang (Elsevier, 2023)
Background/purpose: The coronavirus disease 2019 gradually slows down. As schools now progressively went back to the physical class, it was essential to think about whether we should go back to the physical course, shift to the online course, or try to combine both. Materials and methods: One hundred and six students (including 67 medical students, 19 dental students, and 20 students from another department) who took the histology course with both physical and online lectures and the virtual microscopy for the histology laboratory course were enrolled in this study. Students' acceptance and learning effectiveness were evaluated by a questionnaire-based survey, and their examination scores were compared before and after the online class. Results: Most students accepted the combined physical and online lectures (81.13%), considered increased interactivities in the physical class (79.25%), and felt comfortable when taking the online class (81.14%). Moreover, most students considered that the online learning was friendly to use (83.02%) and could improve the learning effectiveness (80.19%). The mean examination scores were significantly higher after the online class than before the online class, regardless of different genders and groups of students. Most participants (29.2%) preferred the 60% online learning proportion, followed in a descending order by the 40% online learning (25.5%) and the 80% online learning (14.2%). Conclusion: Our students can generally accept the combined physical and online lectures for learning the histology course. The academic performances significantly improve after the online class. The hybrid course may become the future trend of learning the histology course.